Effects of Low-Protein Diet Supplemented with Fermented Feed on Meat Quality, Fatty Acid Composition, and Gut Microbiota in Growing–Fattening Pigs - Qidong Zhu; Xiaorong Zhou; Dingbiao Long; Laifu Leng; Rong Xiao; Renli Qi; Jing Wang; Xiaoyu Qiu; Qi Wang (Agriculture, 2025)
Fermented feed has considerable potential as a high-quality protein source in animal production. This research aimed to examine the effects of a low-protein (LP) diet, supplemented with fermented feed, on the meat quality and intestinal health of growing–fattening pigs. The pigs were randomly divided into three groups, and a total of 72 growing–fattening pigs were subjected to the experiment. They were fed the control (CON) diet, LP diet, and LP diet supplemented with fermented rapeseed meals and fermented distiller’s grains (FLP), respectively. The results indicated that the FLP diet altered the structure of the intestinal microbiota and regulated the composition of unsaturated fatty acids in the longissimus dorsi. Furthermore, the FLP diet upregulated the expression of genes associated with myosin heavy chain isoforms (p < 0.05) and modified the content of short-chain fatty acids in the intestines (p < 0.05). In summary, the addition of fermented distiller’s grains (FDGs) and fermented rapeseed meals (FRMs) to the LP diet enhanced fatty acid metabolism and intestinal barrier function in growing–fattening pigs.